Optimal Sizing and Siting of Multiple Dispersed Generation System Using Metaheuristic Algorithm - Yadav L.K.; Verma M.K.; Joshi P. (My University, 2025)
Optimally sized and sited DGs improve efficiency & the voltage scenario of any radial distribution system (RDS). Optimal DG allocation and sizing problem may be solved by selecting a suitable meta heuristic optimization technique. In this article a hybrid particle swarm optimization-gray wolf optimization (PSO-GWO) is used for optimal placement and sizing of DG units. A multi-objective function is framed utilizing weighted sum of voltage stability index, real power loss and voltage deviation whose weights are optimized using Genetic Algorithm. The proposed methodology is tested on IEEE 33 bus RDS for Type-I DGs. The results obtained demonstrate that PSO-GWO has a clear advantage over other similar techniques. © 2021, Springer Nature Switzerland AG.